The 5 O'clock Band - Andrews, Troy; Taylor, Bill, 1971- (Abrams Books for Young Readers, 2018)
After letting his band down by missing rehearsal, Shorty has some serious questions about what it means to be a leader so he hits the New Orleans streets to find some answers.